A wave‐dominated, tide‐modulated model for the Lower Ordovician of the Anti‐Atlas, Morocco. Issue 3 (11th December 2016) - Vaucher, Romain; Pittet, Bernard; Hormière, Hélène; Martin, Emmanuel L. O.; Lefebvre, Bertrand
Abstract: Hybrid depositional systems are created by the interaction of two or more hydrodynamic processes that control facies distribution and their characteristics in terms of sedimentary structures and depositional geometry. The interaction of wave and tide both in the geological sedimentary record and modern environments has been rarely described in the literature. Mixed coastal environments are identified by the evidence of wave and tidal structures and are well identified in nearshore environments, while their recognition in lower shoreface–offshore environments lacks direct information from modern settings. Detailed field analyses of 10 stratigraphic sections of the Lower Ordovician succession (Fezouata and Zini formations; Anti‐Atlas, Morocco) have allowed the definition of 14 facies, all grouped in four facies zones belonging to a storm‐dominated, wave‐dominated sedimentary siliciclastic system characterized by symmetrical ripples of various scales. Peculiar sedimentary organization and sedimentary structures are observed: (i) cyclical changes in size of sedimentary structures under fair‐weather or storm‐weather conditions; (ii) decimetre‐deep erosional surfaces in swaley cross‐stratifications; (iii) deep internal erosion within storm deposits; (iv) discontinuous sandstone layers in most depositional environments, and common deposition of sandstones with a limited lateral extension, interpreted to indicate that deposition at all scales (metric to kilometric) is discontinuous; (v) combined flow–oscillation ripples showing aggrading–prograding internal structures alternating with purely aggrading wave ripples; and (vi) foreshore environments characterized by alternating phases of deposition of parallel stratifications, small‐scale and large‐scale ripples and tens of metres‐wide reactivation surfaces. These characteristics of deposition suggest that wave intensity during storm‐weather or fair‐weather conditions was continuously modulated by another controlling factor of the sedimentation: the tide. However, tidal structures are not recognized, because they were probably not preserved due to dominant action of storms and waves. A model of deposition is provided for this wave‐dominated, tide‐modulated sedimentary system recording proximal offshore to intertidal–foreshore environments, but lacking diagnostic tidal structures.